2014
DOI: 10.1016/j.jenvman.2014.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualizing ‘effectiveness’ in environmental projects: Can we measure values-related achievements?

Abstract: There have been recent calls for a shift to an evidence-based paradigm in environmental management, grounded in systematic monitoring and evaluation, but achieving this will be complex and difficult. Evaluating the educational components of environmental initiatives presents particular challenges, because these programs often have multiple concurrent goals and may value 'human outcomes', such as value change, which are intangible and difficult to quantify. This paper describes a fresh approach based on co-crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 50 publications
0
43
0
6
Order By: Relevance
“…The project used an emancipatory action research approach, working with organizations and businesses engaged in providing non-formal education for sustainable development (ESD). The latter considered themselves unable to articulate "intangible" aspects of their work which they nonetheless considered key, and the work focused on co-developing an approach that could be highly localized (but also generalized and transferable to some extent) [5,[32][33][34][35] which later became known as WeValue.…”
Section: Purpose Paradigm and Context Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The project used an emancipatory action research approach, working with organizations and businesses engaged in providing non-formal education for sustainable development (ESD). The latter considered themselves unable to articulate "intangible" aspects of their work which they nonetheless considered key, and the work focused on co-developing an approach that could be highly localized (but also generalized and transferable to some extent) [5,[32][33][34][35] which later became known as WeValue.…”
Section: Purpose Paradigm and Context Of This Studymentioning
confidence: 99%
“…Considering the potential importance of effectively bringing values into organizational practices, the authors identified the need for a systematic follow-up study to explore the impacts of the WeValue intervention within a broader organizational context (rather than focusing specifically on project evaluation in relation to non-formal ESD, which has been discussed in depth by Harder et al [33]). It is the findings of this follow-up study, based on a re-analysis of the original dataset, which we report in this paper.…”
Section: Purpose Paradigm and Context Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We thus analyse it for relevance and coverage of Target 4.7, denoting it the ESDinds set, and the approach as 'values-based'. This process produced not rigid indicators, but 'proto-indicators'-reflecting the concept of a 'prototype' in design literature, to refer to concise statements that can serve as templates or triggers for the local development of immediately relevant measurable indicators [33].…”
Section: Values-based Approaches To Indicator Designmentioning
confidence: 99%
“…By investigating different groups of local residents from multiple levels of the society, the study builds up an improved urban environmental management system, combining top-down and bottom-up approaches for better urban development directed at sustainability. The synthesis of the top-down and bottom-up approaches is conducive to the effectiveness of environmental management as the two approaches complement each other (Böhringer and Rutherford, 2008;Harder et al, 2014;Zhang et al, 2011). …”
Section: Systems Thinking With Multi-level Perspectivementioning
confidence: 99%